2007
DOI: 10.1007/s00374-007-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-solubilization activity of bacterial strains in soil and their effect on soybean growth under greenhouse conditions

Abstract: The efficiency of 13 phosphate-solubilizing bacteria (PSB; four Burkholderia sp., five Enterobacter sp., and four Bradyrhizobium sp.) was assessed in a soil plate assay by evaluating soil phosphorus (P) availability. A commercial argentine strain, Pseudomonas fluorescens, was used for comparing solubilizing activity. Burkholderia sp. PER2F, Enterobacter sp. PER3G, and Bradyrhizobium sp. PER2H strains solubilized the largest quantities of P in the soil plate assay after 60 days as compared with the other strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(89 citation statements)
references
References 19 publications
1
82
0
6
Order By: Relevance
“…2004). Similarly, PSB strains were reported to vary in phosphate solubilization activity and 389 stimulating growth of soyabean (Fernández et al 2007). Reddy and Raju (2006) found that 390 application of PSB with PR produced rice yields statistically at par with that produced by SSP 391 application @ 30 kg ha -1 .…”
mentioning
confidence: 99%
“…2004). Similarly, PSB strains were reported to vary in phosphate solubilization activity and 389 stimulating growth of soyabean (Fernández et al 2007). Reddy and Raju (2006) found that 390 application of PSB with PR produced rice yields statistically at par with that produced by SSP 391 application @ 30 kg ha -1 .…”
mentioning
confidence: 99%
“…Increased growth and P uptake of several crop plants due to PSB inoculation have been reported in a number of studies conducted under both growth chamber and greenhouse conditions (Dey et al, 2004;Fernández et al, 2007;Vikram and Hamzehzarghani, 2008;Hariprasad and Niranjana, 2009;Yu et al, 2011). The increase in shoot length, root length, shoot dry weight, and root dry weight of mung bean plants inoculated with PSB strains could be attributed to a greater absorption of nutrients, especially P. Compared with single inoculation, co-inoculation showed higher growth performances and P uptake; this suggests that both strains acted synergistically with each other to promote mung bean plant growth.…”
Section: Discussionmentioning
confidence: 93%
“…Screening of potential phosphate solubilizing isolates, which can be used as bio-inoculants to increase plant growth and yield, is recognized as an area of interest because such microbial inoculants could substantially reduce the chemical fertilizer requirement. There are several previous reports dealing with the application of phosphate solubilizing bacteria (PSB), either individually or combined, to assess their effects on the growth and biomass production of several crops (Fernández et al, 2007;Mittal et al, 2008;Vikram and Hamzehzarghani, 2008;Hariprasad and Niranjana, 2009;Jain et al, 2010). In the present study, we isolated and identified PSB strains and assessed their effect on the growth and nutrient uptake of mung bean plants cultivated under greenhouse conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Sterilized seeds were then placed in glass Petri dish and coated with bacterial suspension (OD 620nm 0.9). Three inoculated seeds were sown per 10 kg of unsterilized soil in earthen pots (Fernández et al, 2007).…”
Section: Pot Culture Experimentsmentioning
confidence: 99%